Implikasi Pengawasan Muatan Terhadap Stabilitas Kapal Penumpang di KM. Madani Nusantara - Makmur Syam; Sahabuddin Sunusi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The purpose of this study was to determine the level of cargo control at KM Madani Nusantara at Parepare Port, causing over load and over dimension in relation to ship stability and safety. PT. Prima Vista is a private shipping company engaged in the transportation of goods and services, especially passenger and vehicle transportation services. Along with the demands of today's modern society, transportation, especially sea transportation related to passenger safety and passenger service, has experienced many developments in terms of the quality and safety of modern, fast sea transportation which is no less important than the demands for comfort while on a cruise. km. Madani Nusantara is one of the Ro-Ro ships owned by PT. Prima Vista which connects Sulawesi and Kalimantan. This study uses a descriptive method that describes certain events that occurred in KM Madani Nusantara. The writer on this ship works as a captain. The results of this study indicate that in the control of cargo on the KM Madani Nusantara ship there is often a load that is not in accordance with the specified capacity or known as over loading and over dimension which is abbreviated as ODOL so that it can cause the ship to tilt.